Heat Transfer Phenomena in Laminar Wavy Falling Films: Thermal Entry Length, Thermal-Capillary Metastable Structures, Thermal-Capillary Breakdown - Lel, Viacheslav V.; Kneer, Reinhold (IntechOpen, 2011)
None